Effects of predamage on the compression performance of CFRP-confined rectangular steel reinforced concrete columns. (1st May 2018) - Gao, Peng; Wang, Jian; Li, Zhongyuan; Hong, Li; Wang, Zhiliang
Highlights: Both the CFRP strain and peak load of columns decreased with the predamaged level. The descending load-displacement curves turned to hardening with increasing CFRP. The sectional concrete confinement is mainly in corners and area surrounded by steel. Abstract: This study investigates the axial compressive behavior of predamaged steel reinforced concrete (SRC) rectangular short columns confined by carbon fiber reinforced polymer (CFRP) laminates. The authors tested 13 large-scale CFRP confined SRC columns. The primary variables were the predamage level and number of CFRP's layers. All confined columns failed in the mode of CFRP laminates rupture after peak load. Both the working strain of CFRP and the peak load of columns decreased with predamage level. This paper also presents a new finite element numerical model for the nonlinear analysis of confined columns. This model was verified against experimental results, which led to the adoption of concrete damaged plasticity model (CDP). Simulation confirmed that the confinement effects of concrete provided by CFRP laminates is mainly restricted in the corner zones and the core area surrounded by the steel in column sections. Both the circumferential CFRP strains and confined concrete compressive stress significantly decreased with the increasing predamage level under peak load states.